Progress and Future Trend of Technologies Used by RAN for 3GPP IoT NTN - ZHANG Lu; WANG Xue; QI Dongqing; WANG Gaojian; YAN Kaiyue; MANG Ge; ZHONG Hua; ZHANG Yang; ZHU Xuetian (天地一体化信息网络)
Satellite IoT not only plays a supplemental role when there have been deployments of terrestrial IoT, but also has some unique advantages, such as promoting the development of low-altitude economy, having a greater tolerance to natural disasters. Aiming at narrow-band satellite IoT services which dominates the market for satellite IoT, in Rel-17, 3GPP issued international standard for IoT NTN for the first time with which NTN can support narrow-band IoT services. Focusing on RAN for 3GPP IoT NTN, this paper will firstly summarize the technical progress in 3GPP Rel-18 which has been officially published in 2024 June, then introduce the technical topics in 3GPP Rel-19, and finally look into the technology trend in 3GPP Rel-20+.